Selected Bibliography Of Literary Works, 2022 - ICW, UP (Likhaan: The Journal of Contemporary Philippine Literature; Vol 16 No 01 (2022): LIKHAAN 16: The Journal of Contemporary Philippine Literature, 2023)
Selected Bibliography Of Literary Works, 2022